Didactic Foundations for Developing Metacognitive Skills in Biology Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the didactic foundations of developing metacognitive skills in biology education. During the study, metacognitive strategies such as reflective journals, concept maps, and question–answer discussions were applied. The results indicated that these methods positively influenced students’ ability to consciously manage their learning process, recognize and correct mistakes, and enhance scientific thinking. The paper substantiates the importance of the metacognitive approach in improving the effectiveness of the learning process based on pedagogical and biological perspectives.